PERBANDINGAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION DAN MAKE A MATCH - Muji Aprilia Fitriani; I Komang Winatha; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This research aimed to determine whether there is a difference between the use of problem-based instruction and make a match models against students' economic learning outcomes and to determine differences in the effectiveness of the use of problem based instruction learning model and make a match the learning outcomes of economics class XI SMA Negeri 1 Sumberjaya. The method used in this study is the method of comparative research with experimental approaches. The test results of the first hypothesis with ANOVA test obtained Sig. 0.0160.05 indicates that there are differences between students' economic learning outcomes with treatment of problem based learning model of instruction and make a match learning models. As for the second hypothesis with manual calculations using formulas obtained results is 1.02, which means that the effectiveness of the use of problem-based instruction model is more effective than make a match models.Penelitian ini bertujuan untuk mengetahui apakah ada perbedaan antara penggunaan model problem based instruction dan make a match terhadap hasil belajar ekonomi siswa dan untuk mengetahui perbedaan efektivitas penggunaan model pembelajaran model problem based instruction dan make a match pada hasil belajar ekonomi kelas XI SMA Negeri 1 Sumberjaya. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian komparatif dengan pendekatan eksperimen. Hasil uji hipotesis yang pertama dengan uji Anava diperoleh Sig. 0,016 0,05 menunjukkan bahwa ada perbedaan hasil belajar ekonomi antara siswa dengan perlakuan model pembelajaran problem based instruction dan model pembelajaran make a match. Sedangkan untuk hipotesis kedua dengan perhitungan manual menggunakan rumus diperoleh hasil keefektifan adalah 1,02 yang artinya penggunaan model problem based instruction lebih efektif dibandingkan model make a match.Kata kunci: hasil belajar, make a match, problem based instruction